移植拒絶反応のリスクを処置または低減する方法 (2025)
本開示は、抗ＣＤ４０抗体またはその抗原結合断片（例えば、ヒト化抗ＣＤ４０抗体またはその抗原結合断片）などの、ＣＤ４０またはＣＤ１５４を標的とするアンタゴニストを投与することによって、それを必要とする対象（例えば、ヒト）において、移植拒絶反応のリスクを処置もしくは低減するか、または移植拒絶反応が発生する前の期間を延長させる方法に関する。移植片は、同種移植片または異種移植片（例えば、細胞、組織、もしくは臓器、またはそれらの一部）であってもよい。【選択図】なし The present disclosure relates to methods of treating or reducing the risk of transplant rejection or increasing a duration of time before transplant rejection occurs in a subject in need thereof (e.g., a human) by administering an antagonist that targets CD40 or CD154, such as an anti-CD40 antibody or an antigen-binding fragment thereof (e.g., a humanized anti-CD40 antibody or antigen-binding fragment thereof. The transplant may be an allogeneic or xenogeneic transplant (e.g., a cell, tissue, or organ or portion thereof).